The evaluation of psychometric properties of the Polish version of the Brief Fatigue Inventory among patients diagnosed with lung cancer - Życińska, Jolanta; Januszek, Maciej; Kudłacik, Magdalena; Pawlak, Adam (Psychoonkologia, 2016)
Introduction : Fatigue is one of the most common symptom reported by cancer patients. The Brief Fatigue Inventory (BFI; Mendoza, Wang, Cleeland, Morrissey, Johnson, Wendt, Huber, 1999) is a short and comprehensive instrument to assess severity of fatigue and fatigue-related impairment in cancer patients. Aim: The aim of the study was to evaluate the psychometric properties of the Polish version of the BFI, and to determine the structure of the tool and its reliability in a group of cancer patients. Material and methods : A total of 200 hospitalized patients participated in the study (55% male) with mean age of 63 years (SD = 10.29), including 66 patients undergoing diagnostics, 70 – during the initial treatment and 64 – undergoing treatment due to recurrence/metastasis of lung cancer. Results and conclusions : The exploratory factor analysis confirmed the one-factor structure of the BFI. High factor loadings were obtained for each item (not less than 0.73), which translated into high reliability coefficients (Cronbach’s α > 0.90). The comparison of fatigue levels between groups of patients indicated statistically significant differences in relation to the impact of fatigue on different aspects of patient’s life, although the magnitude of the effect (η 2 ) did not exceed 5%. The post-hoc test analysis confirmed worse functioning of the patients undergoing treatment due to the recurrence/metastasis of cancer in comparison with the patients undergoing diagnostics. On the basis of the obtained results one may state that the BFI is a reliable tool in the evaluation of fatigue and that during the treatment due to recurrence/metastasis of lung cancer it may reflect patient limitations in everyday functioning.